Social profi le of the unifi ed health system user in primary health care - Aline Braido Pereira; Karen Mello de Mattos; Ruth Maurer da Silva; Juliana Silveira Colomé (Universidade de Santa Cruz do Sul, 2012)
Rationale and Objectives: The Brazilian Unified Health System (SUS) was established as a policy for the general population. Knowledge of the user profile is crucial for your organization. Thus, the aim of this study was to outline the social profile of SUS users in Primary Health Care in the city of Santa Maria/RS. Methods: Descriptive study, carried out in a Family Health Strategy (FHS) unit and a Basic Health Unit (BHU) in the city of Santa Maria/RS from March to April 2010, which included adult users of both genders. Results: A total of 112 users participated in the survey. The highest demand for health care services was at the emergency/urgency care; regarding the users' opinion about SUS services, 60% of BHU users considered it bad and 40.4% of the FHS users considered it good. Conclusion: It is the responsibility of the workers, users and supporters of a theory on health production to try to build projects aiming at the needs, as well as the means to meet them. KEYWORDS: Health Evaluation. Human Resources in Health Care. Health Services. Unifi ed Health System.